Extracellular vesicle separation from milk and infant milk formula using acid precipitation and ultracentrifugation - Mukhopadhya, Anindya (My University, 2021)
Separation of highly enriched extracellular vesicles (EVs) fractions from milk is desirable for quantification, cargo analysis, functional characterization, and investigation as delivery vehicles for nutrients and/or therapeutics. However, a rigorous, reproducible protocol is lacking. This protocol considers a crucial aspect typically overlooked, i.e., that caseins are of similar size to, but more abundant than, EVs in milk. Our protocol combines acid pre-treatment and gradient ultracentrifugation, producing EV-enriched fractions suitable for downstream orthogonal characterization approaches. For complete details on the use and execution of this protocol, please refer to Mukhopadhya et al. (2021).
PUBLISHED
Keywords: Health Sciences; Molecular Biology; Protein Biochemistry; Protein expression and purification; Biotechnology and bioengineering; Cancer; Immunology, Inflammation & Infection; Nanoscience & Materials